Етнічна належність у наукових теоріях - Савонякайте, В. (Народна творчість та етнологія, 2011)
The paper deals with the rise of an ethnicity notion in the history of ethnological and anthropological sciences. It discusses the main theoretical approaches to ethnicity in the contemporary Lithuanian ethnology and current anthropological researches. The aim of the paper – to analyze how a constructive notion of ethnicity functions in the Lithuanian ethnological and anthropological researches and how an ethnicity is dependent on the specific everyday situations among the contemporary Lithuanian groups and marginal ethnic Lithuanian groups.